(untitled) (Research, Society and Development, 2022)
Objective: To report the experience of nursing students during a nursing consultation with women for cervical and breast cancer screening in a Primary Health Care unit. Method: this is an experience report in a practical discipline of women’s health, carried out in a Basic health unit located in the municipality of Juiz de Fora. In this report, the practica and reflective exercise of future nursing professionals translate the knowledge and the theory in a context of isolation and uncertainties imposed in a pandemic. Conclusion: the practical teaching of women’s care involves technical, theoretical, and practical knowledge, the latter acquired during care activities, where the future nursing professional develops socio-emotional and communication skills. Both are necessary to overcome the fragmentation of assistance and strengthen the empowerment of women in a nursing consultation for cervical and breast cancer screening.